2018
DOI: 10.1002/mnfr.201800060
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ANGPTL‐4 is Associated with Obesity and Glucose Tolerance: Cross‐Sectional and Longitudinal Findings

Abstract: Our data support a relevant role of ANGPTL-4 in human obesity and its involvement in long-term body weight changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 34 publications
(54 reference statements)
2
39
0
Order By: Relevance
“…Elevated circulating levels of ANGPTL4 and TAGs are key etiologic components of metabolic disorders like obesity, T2D, and CAD, which are associated with increased adiposity, fatty liver, and insulin resistance. Human studies indicate a positive relationship between ANGPTL4 function and body mass index (BMI), fat mass, glucose intolerance, insulin resistance, and circulating lipids (25). These observations strongly suggest that ANGPTL4 could be a potential target in metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Elevated circulating levels of ANGPTL4 and TAGs are key etiologic components of metabolic disorders like obesity, T2D, and CAD, which are associated with increased adiposity, fatty liver, and insulin resistance. Human studies indicate a positive relationship between ANGPTL4 function and body mass index (BMI), fat mass, glucose intolerance, insulin resistance, and circulating lipids (25). These observations strongly suggest that ANGPTL4 could be a potential target in metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in humans have shown that loss of function mutations in the ANGPTL4 locus are associated with reduced type 2 diabetes and risk of cardiovascular disease (21,25). However, mice lacking ANGPTL4 and fed a high fat diet enriched in saturated fat develop gut inflammation, characterized by the accumulation of lipid-laden macrophages.…”
Section: Galnac-conjugated Angptl4 Aso Treatment Improves Body Weightmentioning
confidence: 99%
See 2 more Smart Citations
“…Angiopoietin-like protein 4 (ANGPTL4) was first discovered in 2000 [5] as a novel member of the angiopoietin family. Under physiological conditions, ANGPTL4 functions as a key regulator of lipid metabolism and its role has been widely reported in metabolic diseases and cardiovascular diseases [6,7]. In addition, some studies have reported that ANGPTL4 plays a significant role in tumor invasion, intestinal microecological regulation, fracture healing, and tendon cell proliferation, adhesion, and migration [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%